Brain network functional connectivity changes in long illness duration chronic schizophrenia - Bai, Yin Xia; Luo, Jia Xin; Peng, Duo; Sun, Jing Jing; Gao, Yi Fang; Hao, Li Xia; Tong, B. G.; He, Xue Mei; Luo, Jia Yu; Liang, Zi Hong; Yang, Fan (Frontiers in Psychiatry, 2024)
Chronic schizophrenia has a course of 5 years or more and has a widespread abnormalities in brain functional connectivity. This study aimed to find characteristic functional and structural changes in a long illness duration chronic schizophrenia (10 years or more). Thirty-six patients with a long illness duration chronic schizophrenia and 38 healthy controls were analyzed by independent component analysis of brain network functional connectivity. Correlation analysis with clinical duration was performed on six resting state networks: auditory network, default mode network ,dorsal attention network , fronto-parietal network , somatomotor network , and visual network . The differences in the resting state network between the two groups revealed that patients exhibited enhanced inter-network connections between default mode network and multiple brain networks, while the inter-network connections between somatomotor network, default mode network and visual network were reduced. In patients , functional connectivity of Cuneus_L was negatively correlated with illness duration. Furthermore, receiver operating characteristic curve of functional connectivity showed that changes in Thalamus_L, Rectus_L, Frontal_Mid_R, and Cerebelum_9_L may indicate a longer illness duration chronic schizophrenia . In our study, we also confirmed that the course of disease is significantly associated with specific brain regions, and the changes in specific brain regions may indicate that chronic schizophrenia has a course of 10 years or more.